Lipoid Proteinosis with Esotropia: Report of a Rare Case and Dermoscopic Findings - Hera Tabassum; Sabha Mushtaq; Syed Suhail Amin; Mohammad Adil; Mohammad Mohtashim; Kafil Akhtar (Wolters Kluwer Medknow Publications, 2020)
Lipoid proteinosis (LP) is a rare progressive autosomal recessive disorder caused by mutations in the extracellular matrix protein 1 gene present on chromosome 1q21. It is characterized by infiltration of hyaline material into the skin, mucosae, and internal organs. Patients present with a classical history of repeated blistering, skin scarring, beaded eyelid papules, waxy papules over the body, and laryngeal and tongue infiltration leading to hoarseness of voice and restricted tongue movement. A variety of ocular manifestations have been described in association with LP. We report a case of a 10-year-old female child with typical features suggestive of LP associated with unilateral esotropia. The case is reported here for its rarity and uncommon association with esotropia hitherto not documented. Dermoscopic findings of the case are also discussed.